Melayani Tuhan di Tempat Kerja - Sugiyarto, Iskak (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2021)
The adaptation of new habits due to the corona virus pandemic applies to the world community and Indonesia. Adaptation affects the relationship between individuals, so that the pattern of interaction in society requires adjustment. This is no exception for churches and Christian institutions in service to the congregation and to society. Service models with the old approach - especially before the corona virus pandemic - need to be evaluated to find patterns that fit the community in this new normal. Therefore, this study wants to find out how churches and Christian institutions should serve in adapting new habits during this corona virus pandemic? How does the church involve a congregation of mostly lay and secular workers serving in the world of work? By using a study of literature or literature, it is expected to find a pattern of church service (eklesia) that is in accordance with the conditions of today's society. From literature studies and previous research, it was found that a growing church is a church that does not only rely on "the robed people", but involves all lay people, namely "secular workers" to serve routine activities within the church, as well as services outside the church ( workplace).AbstraksiAdaptasi kebiasaan baru akibat pandemi virus korona berlaku bagi masyarakat dunia dan Indonesia.  Adaptasi itu mempengaruhi hubungan antar individu,  sehingga pola interaksi di masyarakat yang perlu adanya penyesuaian.  Hal ini tidak ada pengecualian bagi gereja dan lembaga-lembaga Kristen dalam pelayanan kepada jemaat serta kepada masyarakat.  Model-model pelayanan dengan pendekatan lama - secara khusus sebelum pandemi virus korona - perlu dievaluasi untuk menemukan pola yang sesuai dengan masyarakat di new normal ini.  Oleh sebab itu, penelitian ini ingin mencari tahu bagaimana gereja dan lembaga-lembaga Kristen seharusnya melayani pada adaptasi kebiasaan baru saat pandemi virus korona ini?  Bagaimana gereja melibatkan jemaat yang umumnya kaum awam dan pekerja sekuler melayani di dunia kerja? Dengan menggunakan studi literatur atau kepustakaan diharapkan menemukan pola pelayanan gereja (eklesia) yang sesuai dengan kondisi masyarakat saat ini.  Dari studi literatur dan penelitian sebelumnya ditemukan bahwa gereja yang bertumbuh adalah gereja yang tidak hanya mengandalkan “kaum berjubah”, melainkan melibatkan semua kaum awam, yaitu para “pekerja sekuler” untuk melayani kegiatan-kegiatan rutin di dalam gereja, serta pelayanan di luar gereja (tempat kerja).